1997
DOI: 10.2307/2410959
|View full text |Cite
|
Sign up to set email alerts
|

Long-Tongued Fly Pollination and Evolution of Floral Spur Length in the Disa draconis Complex (Orchidaceae)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Society for the Study of Evolution is collaborating with JSTOR to digitize, preserve and extend access to Evolution.Abstract.-Field studies in South Africa showed that floral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
218
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(235 citation statements)
references
References 20 publications
11
218
2
4
Order By: Relevance
“…Nevertheless, it is possible that there has been adaptation of the cycads to cryptic weevil species, which would be a case of divergence driven by shifts in pollinators, rather than coevolution [49,50]. However, a recent molecular study of phylogenetic relationships within Porthetes spp.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is possible that there has been adaptation of the cycads to cryptic weevil species, which would be a case of divergence driven by shifts in pollinators, rather than coevolution [49,50]. However, a recent molecular study of phylogenetic relationships within Porthetes spp.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated a close match between flower and pollinator morphology, such as correlations between proboscis length of pollinators and corolla depth of flowers on the scale of species-specific interactions, that have served as supposed examples of coevolution (Alexandersson and Johnson 2002;Grant andGrant 1965, 1983;Harder 1985;Johnson and Steiner 1997;Nilsson 1988Nilsson , 1998Nilsson et al 1985). Although our results showed that the proboscis lengths of skipper butterflies differed significantly between the visited flower species, we did not observe a close match between extremely long proboscides and deep tubes: Extremely long-proboscid skipper butterflies that used C. crotalifera and C. lutea as nectar source had a mean proboscis length of 43.4 mm, exceeding the corolla length of C. crotalifera by 18.4 mm and C. lutea by 12 mm.…”
Section: S Frantziimentioning
confidence: 99%
“…For nearly all of these radiations, there exists an outlier species, with extremely long mouthparts, that visit plants with flowers of a corresponding length. Examples include the sword-billed hummingbird (Ensifera ensifera) with a 10 cm long bill (Snow & Snow 1980), the mega-nosed fly (Moegistorynchus longirostris) with a 5.7 cm long proboscis ( Johnson & Steiner 1997) and the giant hawkmoth (Xanthopan morgani praedicta) with a 25 cm long proboscis ( Nilsson et al 1985). Darwin (1862) and Wallace (1867) provided a possible explanation for such extreme elongation, suggesting that the long nectar spur of the Malagasy star orchid (Angraecum sesquipedale) evolved in a coevolutionary race with a giant hawkmoth.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have provided support for Darwin's hypothesis by demonstrating instances of pollinators imposing directional selection on flower length ( Nilsson 1988;Johnson & Steiner 1997;Alexandersson & Johnson 2002;Anderson & Johnson 2008). However, the hypothesis has also met with resistance since it was first published, and various alternative models have been proposed.…”
Section: Introductionmentioning
confidence: 99%